ANALYSIS OF INFANT MILK FORMULA IN MANADO USING PERCEPTUAL MAPPING - Mononimbar, Monica Sharen; Tielung, Maria V.J. (FEB Universitas Sam Ratulangi Manado, 2014)
Positioning is a fundamental component of marketing planning and business strategies making. Product positioning is the process marketers use to determine how to best communicate their products attributes to their target customers based on customer needs, competitive pressures, available communication channels and carefully crafted key messages. Indonesia population growth rate is at one percent by 2013 est. Nutritional scientists and pediatricians recommend that infants should consume milk or formula. Infant formula is the substitute product to breastfeeding, and in the market industry of infant formulas there are many brands competing in the industry. The purpose of this research are to determine and show the brand positioning of each brand of infant formulas that exist in the market in Manado by using perceptual mapping which contain multidimensional scaling and correspondence analysis method with 100 respondents as sample of the research. SGM, Lactogen, Nutrilon, Enfagrow, S26 and Nan are the infant formulas brands that are studied. Price and Quality are the attributes used in studying infant formula brand in this research. Based on Perceptual Mapping, demographics of age and occupation correlate with customer perception of the brands. Different age and different occupation may perceive different preferences and perception on the infant formula brands / products. Keywords: consumer perception, perceived price, perceived quality.